NILAI PENDIDIKAN RELEGI DALAM SEKAR RARE - Ni Wayan Murniti (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
Good culture needs to be identified and maintained. These cultural forms in the contextof their preservation need to be explored in depth. Related to sekar rare is very closely related tothe belief in Ida Sang Hyang Widhi Wasa and the srada bhakti aspect. Based on this existence, itis necessary to conduct a study of the literature of the song, especially Sekar Rare. The center ofattention is Religious education in Sekar Rare. Based on the existence of Sekar Rare, the divisioncan be identified based on its shape and characteristics, namely: Gending Rare, Gending Janger,and Gending Sanghyang. Sekar Rare can also be used as an educational medium including: Therole as an educational medium for the introduction of language structures, as a medium for theintroduction of the environment, as a medium for the introduction of nature, as a medium forcharacter formation. In addition, in Sekar Rare the values ??of religious education include; thevalue of religious education related to ethics and character and the value of religious educationare related to the concept of karmapala.